TINGKAT PENERAPAN PRINSIP-PRINSIP BIMBINGAN DALAM KEGIATAN BIMBINGAN DI LINGKUNGAN PERGURUAN TINGGI DIHUBUNGKAN DENGAN ORIENTASI NILAI BUDAYA DAN SIKAP TERHADAP BIMBINGAN DOSEN PEMBIMBINGA PADA BEBERAPA PERGURUAN TINGGI - Roosd Achmad Syuhada, - (1985)
Since 1980, the guidance has formally been adopted as an integral part of the total higher educational program. According to the Director General of Higher Education, guidance and counseling programs at the universities and institutes will be developing much more steadily.In fact, the outcome of the practice of guidance programs in some higher educational institutions is still far from the expected goal because of many obstacles: lack of fully-qualified full-time counselors, lack of comprehensiveness in the programs, minimal facilities, and a low level of the use of principles of guidance. The Problems The present study is focused on the following main problems: 1. To what extent do personnel counselors' use the principles of guidance in guidance activities on their job? 2. What are the factors which significantly influence the personnel counselors' use of the principles of guidance? Two factors are considered to have a significant influence on the personnel counselors' use of the principles of guidance, i.e.: (a) personnel counselors' value orientation, and (b) personnel counselors1 attitudes towards guidance.Objectives The primary purpose of this research paper is to show empirically the relation among the extent of the use of the principles of guidance, the personnel counselors1 value orientation, and their attitudes towards guidance. The secondary purposes are: 1. To identify the extent of the use of the principles of guidance by personnel counselors at some of the higher educational institutions. 2. To examine personnel counselors' value orientation. 3. To collect information about personnel counselors' attitudes towards guidance. 4. To understand to what extent these three variables are related to each other. Methods In accordance with the puspose of this study and the kinds of data which has been collected, the most appropriate method is the descriptive-analitical method. Three instrumens used for data collecting are: (a) Self Inventory, (b) Values Orientation Scale, and (c) Likert's Attitude Scale model. Methods of analysis used were the multiple correlation and multiple regression equation. The scores for all three instruments, i.e. Self Inventory, Value Orientation Scale, and Attitude Scale, were correlated with each other to assess the level of the use of the principles of guidance.Findings This study has two kinds of finding: (a) the principles of guidance, and (b) empirical information about the three variables. a. The principles of guidance are: 1. Guidance based on democracy as way of life. 2. Guidance for all students. 3. Guidance recognizes and respects individual differences. 4. Guidance utilizes knowledge and concepts of all disciplines that helped it. 5. Guidance emphasises the development of the whole person, 6. Guidance is part of the total educational program. 7. Guidance is client-centered or student-centered. b. The empirical information about the three variables are: 1. Personnel counselors' use of the principles of guidance varies between the mechanical and routine levels, which means that they used principles of guidance without adequate self-involvement or the intention to improve the application of these principles to the students' and institutions 1 expectations, 2. Personnel counselors' value orientation is moderately positive, which means that they have already adopted modern universal values, but are still too bound by traditional values.3. Personnel counselors' attitudes towards guidance were also moderately positive, which means that they have already experienced good feelings about guidance, but are still reluctant to fully apply guidance principles. 4. Personnel counselors' value orientation and attitudes towards guidance have a significant influence on personnel counselors' use of the principles of guidance. This means that if the value orientation and the attitudes towards guidance of personnel counselor can be improved, the extent of the use of principles of guidance will increase. Recommendations Based on the findings of the present study, it is recommended that more appropriate principles of guidance be established in addition to improving value orientation and attitudes towards guidance programs.